2017
DOI: 10.17795/semj43958
|View full text |Cite
|
Sign up to set email alerts
|

Optimizing the Performance of Magnetic Resonance Imaging Department Using Queuing Theory and Simulation

Abstract: Background: The diagnostic services such as Magnetic Resonance Imaging (MRI) require advanced and costly technologies; and making the right managerial decisions to reduce patients' waiting time and increase employees' productivity in providing such services is essential.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 28 publications
(26 reference statements)
0
3
0
Order By: Relevance
“…Another study conducted a DES of the addition of one dosimetrist and reported a 6.55% reduction in the average wait time for radiation treatment in a radiation oncology clinic and an increase in the proportion of patients (84.92%) who would receive treatment within 14 working days. In another DES study, the addition of one MRI scanner and one radiation technologist at a military hospital in Iran resulted in an improvement in the medical personnel’s productivity and the elimination of patient wait time for turn-taking until admission [ 23 ]. In a Canadian study that employed a DES model, increasing the number of physician visits and sleep therapists reduced the wait times for examinations in a sleep therapy center by approximately 28 days [ 24 ].…”
Section: Literature Reviewmentioning
confidence: 99%
See 1 more Smart Citation
“…Another study conducted a DES of the addition of one dosimetrist and reported a 6.55% reduction in the average wait time for radiation treatment in a radiation oncology clinic and an increase in the proportion of patients (84.92%) who would receive treatment within 14 working days. In another DES study, the addition of one MRI scanner and one radiation technologist at a military hospital in Iran resulted in an improvement in the medical personnel’s productivity and the elimination of patient wait time for turn-taking until admission [ 23 ]. In a Canadian study that employed a DES model, increasing the number of physician visits and sleep therapists reduced the wait times for examinations in a sleep therapy center by approximately 28 days [ 24 ].…”
Section: Literature Reviewmentioning
confidence: 99%
“…By contrast, simulations allow for the modeling of real-world environments and systems through the use of software, which enables a proposed solution to be implemented in a simulated model without affecting the current situation and without investment in resources. According to existing simulation-based evaluation studies, three strategies can be applied to shorten long wait times and increase the number of MRI department services that are provided: investing in additional workforce and related resources [7,[23][24][25]; minimizing the idle time of available scanners, rooms, and physicians involved in MRI examinations [8,19,26]; and minimizing the operation time of current services [9].…”
Section: Application Of Simulation To Improve Patient Wait Timesmentioning
confidence: 99%
“…The exact performance indicators that were calculated in their study include the average number of patients referred to the pharmacy and the system utilization rate. Bahadori, Teymourzadeh, Hosseini, & Ravangard (2017) targeted the performance optimization of a magnetic resonance imaging (MRI) department in a hospital using queuing theory and simulation. For assessing the performance measures pertaining to the queuing model (including the queue length and average waiting time), they considered the different workstations that the patients face in this department.…”
Section: Related Workmentioning
confidence: 99%